Do Farm Support Programs Reward Production Inefficiency?. (2nd November 2017) - Hailu, Getu; Poon, Kenneth
Abstract: Agricultural policy frameworks such as Growing Forward are intended to enhance the productivity and competitiveness of the Canadian agricultural sector and to stabilize farm income. This paper examines the relationship between production efficiency and government program payments. First, we find evidence of heterogeneity in production efficiency across farms. Second, we find a negative correlation between production efficiency and the share and level of program payments. The result of this study underscores the importance of understanding the link between technical inefficiency and government payments. Les cadres stratégiques agricoles comme Cultivons l'avenir existent pour favoriser la productivité et la compétitivité du secteur agricole canadien et pour stabiliser les revenus des exploitations agricoles. Cet article examine la relation entre l'efficience de la production et les programmes gouvernementaux de paiements. En premier lieu, nous avons trouvé des preuves d'hétérogénéité dans l'efficience de la production dans toutes les exploitations agricoles. Ensuite, nous avons identifié une corrélation négative entre la production efficiente, et la part et niveau des programmes de paiements. Le résultat de cette étude met en relief l'importance de comprendre le lien entre les inefficiences techniques et les paiements gouvernementaux.